Academic Senate Minutes 2014-11-20 - Academic Senate:::::::::
Agenda approved. Minutes of 11/6/14 – approved. Chair Report. Consent Items: Program Revisions to ENSP and Sociology – approved. Information Item: Info graphic regarding Service in the University. Lecturer's Role in Departmental Governance policy amended and approved. President Report. Vice Chair Report. Questions for the VP of Administration & Finance. Associated Students Report. Statewide Senators Report. EPC Report. FSAC Report. SAC Report. CFA Report. Staff Report. Good of the Order.